"Mantra" by Jennie Kim: A Semiotic Analysis of Women's Confidence in Song Lyrics - Syifa Mediana Putri (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2025)
Women’s confidence can be represented in modern pop music through the selection of language style to overturn the traditional gender expectations in society. For all this time, women have been frequently haunted by beauty standards framed by media and culture that limit their courage to express themselves. This study investigates how women’s confidence is interpreted in the song lyrics of Mantra by Jennie Kim, using semiotics theory to unearth hidden meanings. This research aims to uncover the depiction of women expressing themselves in the song lyrics through the analysis of denotation, connotation, and myth. The discussion focuses on the portrayal of women’s confidence, delivered in certain choices of expressions. The results of this study seem to indicate that the song’s lyrics employ a number of strong images to express women’s self-reliance and courage. Moreover, domination and women's power are also emphasized, successfully opposing the gender expectations that have grown to be the basis of society’s mindsets. Through semiotics, the song Mantra serves as a spell that validates women’s self-confidence as a part of their empowerment. The lyrics’ use of styles in language attempts to generate and convey the meanings to the listeners.